The leader's climb : a business tale of rising to the new leadership challenge - Parsanko, Bob; Heagen, Paul (Bibliomotion, 2012)
"Adam was stuck." And with this simple phrase, The Leader's Climb introduces the reader to an engaging tale of how leaders often ascend quickly to the top, only to unknowingly slip down a path of decline-until it is too late. In this novel approach to the subject, set against the backdrop of a rock-climbing vacation gone awry, executive coaches Bob Parsanko and Paul Heagen draw from decades of success with business executives to reveal an all-too-familiar path of leadership struggles. The protagonist, Adam, is capable and well-meaning but has confidence bordering on hubris, and blind spots that could be the end of him. That is, until unlikely encounters with a park ranger and a home handyman, who become confidants and mentors, reveal new insights to Adam. Through their wisdom, and the realities of the hard knocks of business, Adam gets "unstuck" and begins to turn around his life and career with three fundamental principles of personal growth: awareness, acceptance, and abundance.